Handbook of writing research - MacArthur, Charles A.; Graham, Steven 1950-; Fitzgerald, Jill (The Guilford Press, 2016)
"The definitive reference in the field, this volume synthesizes current knowledge on writing development and instruction at all grade levels. Prominent scholars examine numerous facets of writing from sociocultural, cognitive, linguistic, neuroscience, and new literacy/technological perspectives. The volume reviews the evidence base for widely used instructional approaches, including those targeting particular components of writing. Issues in teaching specific populations, ncluding students with disabilities and English learners, are addressed. Innovative research methods and analytic tools are clearly explained, and key directions for future investigation identified."--Page 4 de la couverture.